Adoção de artefatos da contabilidade de gestão por empresas de pequeno porte : o caso das indústrias do Rio Grande do Sul - Spanholi, Juliane de Castilhos (Universidade do Vale do Rio dos Sinos, 2018)
Over the years industrial companies have been developing more and more complex activities, requiring more quality information for management purposes. Management accounting and its practices have been improved in order to deal with the difficulties imposed by this business environment, seeking new ways to meet the growing need for information in order to support the decision-making process. In this context, the objective of this study is to analyze the adoption of Management Accounting Practices by small companies in the industrial segment of Rio Grande do Sul. The practices were investigated in 26 Brazilian publications, with the purpose of constructing the research instrument based on the most researched practices in previous studies. For this study, a survey was applied to managers of small industrial companies in Rio Grande do Sul, obtaining a return of 155 respondents. The main findings show that the small firms analyzed tend to adopt more absorption costing, variable costing and activity based costing, while BSC e EVA were the least adopted, and the scarcity of financial resources for the implementation and maintenance of the practices was the main difficulty. Through multiple regression it was identified that variable costing and EVA presented significant evidence of a positive relation with performance perception. On the other hand, target costing presented significant evidence of a negative relation to performance, however, this result should be evaluated with caution because all practices tend to increase performance, by providing more information for decision making, improving control of companies.
Keywords: Artefatos da contabilidade de gestão; Empresas de pequeno porte; Indústria; Management accounting practices; Small businesses; Industry; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis